Reading strategies, vocabulary size and reading comprehension of iraqi secondary school efl learners - Alabbaichy, Leena Saad Faaik; Che Mat, Nur Huslinda; Mohd Ramli, Nor Fazlin (GADING Journal for the Social Sciences, 2025)
While research on reading comprehension and the factors influencing EFL learners’ reading performance is construed as crucial for identifying the challenges they encounter, there is a scarcity of work that focuses on secondary school EFL learners, especially Iraqi secondary school EFL students. These studies also emphasized reading strategies and vocabulary size independently of the relationship between these factors and reading comprehension performance, and thus it is still unclear how both reading strategies and vocabulary size contribute to better reading performance. For this purpose, our study has three key objectives: i) to determine what are the reading strategies most frequently used by Iraqi 12th-grade secondary school EFL students, ii) to assess students’ vocabulary size, and iii) to investigate the relationship between reading strategies, vocabulary size, and reading comprehension. Our participants answered a survey of reading strategy, a vocabulary size test, and a reading comprehension test. Our findings revealed that the problem-solving reading strategy was the most popular reading strategy among Iraqi secondary school EFL students. This strategy was also positively and significantly associated with better reading comprehension outcomes. The results also showed that our subjects had a vocabulary size of 2500 words on average, and that vocabulary size was positively and significantly associated with reading performance. In general, these observations provide EFL teachers with useful information about what influences reading comprehension among Iraqi secondary school EFL students and suggest possible areas of research.